Evaluating the width of navigational channels - Paulauskas, Vytautas; Paulauskas, Donatas (Transport, 2013)
The width of a navigational channel is a very important issue for navigational safety, and therefore is calculated on the basis of ship parameters and surroundings. Research on the passes of navigating ships under different conditions is crucial for navigational safety in ports etc. The evaluation of the width of navigational channels under certain circumstances is the main objective of investigation discussed by the authors of this article. The evaluation of the width of navigational channels for big ships coming into Klaipėda port (Lithuania) has been taken as a case study. Also, the received results could be used in other ports and navigational channels. First Published Online: 16 Jul 2013